The Effect of Punishment on Elementary Students in the ‎Islamic School ‎ - Widyastuti Widyastuti (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
This study aims to provide understanding about school’s perceptions of discipline and punishment for elementary students in Bawen and Ambarawa region.  This research used qualitative method to collect the data.  The datas was collected by questionnaire and observation.  The participants consist of students and their parents, also the teachers of elementary school in Bawen and Ambarawa regions.  From the observation could get some different perception about punishment to the children or student in the form. The data collected by some classification, so it obtained a decision of their opinion. The results showed that the physical and verbal punishment as in various forms in classroom for discipline programs.  When the students broke the rules, they would be subject to discipline.  Actually, punishment had some negative side effects to them.  The students who were the object of punishment would showed a bad attitude towards to their teachers and friends.  It could be concluded that punishment is humanistic and educative punishment and the least effective of punishment was authoritarian and non- educative punishment. The teacher should give punishment which would give an educational effect to their student. So, they would get an educational advantages from it.